2020
DOI: 10.1038/s41467-020-17017-7
|View full text |Cite
|
Sign up to set email alerts
|

Tracking down the molecular architecture of the synaptonemal complex by expansion microscopy

Abstract: The synaptonemal complex (SC) is a meiosis-specific nuclear multiprotein complex that is essential for proper synapsis, recombination and segregation of homologous chromosomes. We combined structured illumination microscopy (SIM) with different expansion microscopy (ExM) protocols including U-ExM, proExM, and magnified analysis of the proteome (MAP) to investigate the molecular organization of the SC. Comparison with structural data obtained by single-molecule localization microscopy of unexpanded SCs allowed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 59 publications
(110 reference statements)
1
49
0
Order By: Relevance
“…and stimulated emission depletion (STED) microscopy. The latter combination of which has been employed to study microtubules, [4,5,6] cilia and centrioles [7] . The combination of ExM with these techniques provides a promising tool to disclose details beyond the resolution limit of a super‐resolution microscope.…”
Section: Introductionmentioning
confidence: 99%
“…and stimulated emission depletion (STED) microscopy. The latter combination of which has been employed to study microtubules, [4,5,6] cilia and centrioles [7] . The combination of ExM with these techniques provides a promising tool to disclose details beyond the resolution limit of a super‐resolution microscope.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral view sections, which are equivalent to sites where the SYCP3 signal twists (e, arrowhead), di SIM resolves a splitting of the SYCP1-N signals (Figure S2, Supporting Information). [40,42] Furthermore, di SIM resolves the SC proteins individually both at the pseudo-autosomal region of the XY pair (f) as well as at the unsynapsed regions of the sex chromosomes (g). Scale bars, a) 5 µm, b,c) 1 µm, d-g) 250 nm.…”
Section: Resultsmentioning
confidence: 99%
“…[39] The nanoscale dimensions of the SC have been well characterized by different SR techniques including d STORM [40] and combinations of SR and expansion microscopy. [41,42] However, while SMLM methods are restricted to one-or two-color imaging using suited fluorophores in photoswitching buffer, three-color di SIM with standard fluorophores resolves the organization of the SC with a resolution previously only achieved by three-color SIM of ∼3-fold expanded SCs (Figure 3, Figures S2, S3, Supporting Information). [42] This allowed us to resolve a splitting in the signal of the N-terminally labeled transverse filament protein SYCP1 (SYCP1-N) in lateral views of the SC (Figure 3e).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, several reports (Chozinski et al 2016 ; Cahoon et al 2017 ; Freifiled et al 217; Jiang et al 2018 ; Wang et al 2018b ; Gambarotto et al 2019 ; Kao and Nodine 2019 ; Xu et al 2019 ; Zwettler et al 2020a , b ) demonstrated the improved visualisation of target proteins after applying ExM. Thus, ExM can reveal the unaltered localization of target molecules, but preserving the chromatin ultrastructure of isolated nuclei is more challenging, and therefore, further improved ExM protocols have to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several expansion protocols emerged to increase the expansion factor and to preserve the ultrastructural features. These protocols were adapted to species like fungi, human, mouse, fruit fly and zebrafish and soft tissues such as brain, skin, kidney and liver (Chen et al 2015 ; Tillberg et al, 2016 ; Cahoon et al 2017 ; Freifeld et al 2017 ; Halpern et al 2017 ; Jiang et al 2018 , Lim et al 2019 ; Truckenbrodt et al, 2019 ; Götz et al 2020 ; Zwettler et al 2020b ). The following processes occur during ExM to fix, embed and expand the specimen successfully: (1) during the fixation with a formaldehyde/acrylamide mixture, formaldehyde crosslinks proteins/DNA/RNA to each other; (2) during gelation, the crosslinked proteins become crosslinked to the polyacrylamide (PAA) gel due to the acrylamide provided during fixation; (3) during denaturation in SDS buffer and at high temperature, all crosslinked proteins denature while remaining crosslinked to the PAA gel mesh which starts to expand in the denaturation buffer; (4) during expansion in water, all proteins renature back with gaps between each other but still bound to the PAA gel mesh preserving their exact position as before expansion (Chen et al 2015 ; Cho et al 2018 ; Tillberg and Chen 2019 ; Wassie et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%